Mekanisme Bagi Hasil dalam Usahatani Padi swah di Desa Bou Kecamatan Lambandia Kabupaten Kolaka Timur - Hamsa, Hamsa; Taufik, Yani; Arif, La Ode Kasno (Fakultas Pertanian Universitas Halu Oleo, 2023)
This research is motivated by a cooperation agreement for the profit sharing system in paddy rice farming between land owners and land cultivators which is generally carried out only orally on the basis of trust, without witnesses, not registered by the village head, not ratified by the sub-district and no law binding agreements. The purpose of the study was to determine the profit sharing mechanism in paddy rice farming in Bou village, Lambandia district, East Kolaka regency and find out what obstacles were faced in the implementation of profit sharing for paddy rice farming in Bou village, Lambandia District, East Kolaka regency. The determination of this location is carried out intentionally or purposively with considerations, there are paddy rice farming activities that are managed with a profit-sharing system, profit sharing agreements are still carried out orally, and Lambandia district produces the largest paddy rice production in East Kolaka district. The population in this study was 21 land owners and paddy paddy cultivators in Bou village. The samples in this study amounted to 15 land owners and 15 land cultivators who carried out profit sharing in the cultivation of paddy rice farming. The data analysis used in this study is descriptive. Descriptive analysis is an analysis that explains as a whole the information obtained from the field obtained from interviews and uses tables that are easy to understand, interpret, and compile and present data into clear information where the necessary data comes from the results of answers to questions asked to respondents in the form of questionnaires.